Recent Progress of Novel Electrochemiluminescence Nanoprobes and Their Analytical Applications - Zhang, Shiyu; Liu, Yang (Frontiers in Chemistry, 2021)
High performance nanomaterials have been seen as a new generation of electrochemiluminescence (ECL) probes or emitters for their finely tunable structure and concomitant remarkable properties, guaranteeing the prospective applications in the analysis and diagnosis devices with superior performances. The structure-activity relationships of ECL nanoprobes in nanoscale are presenting milestone in understanding of the ECL microscopic behaviors and mechanisms, and guide the exploitation of novel ECL probes. In this mini-review, we summarized the recent development of novel ECL probes based on the nanomaterials. The mechanism and relationships between their structure as well as the active sites and functionality were revealed. In addition, the design and regulation of the ECL nanoprobes were emphasized for the biosensing and imaging application. Finally, the potential prospect of the ECL nanoprobes design and their applications were discussed.